2023
DOI: 10.1002/adom.202202318
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Imaging Using Inverse Design of Nanophotonic Scintillators

Abstract: Converting ionizing radiation into visible light is essential in a wide range of fundamental and industrial applications, such as electromagnetic calorimeters in high‐energy particle detectors, electron detectors, image intensifiers, and X‐ray imaging. These different areas of technology all rely on scintillators or phosphors, i.e., materials that emit light upon bombardment by high‐energy particles. In all cases, the emission is through spontaneous emission. The fundamental nature of spontaneous emission pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Enhancements in both light yield and decay time have been shown to significantly improve the spatial resolution of Xray imaging, as demonstrated in Refs. [37,39] Since we have developed a Purcell-enhanced scintillator system facilitated by nanoplasmonic design (depicted in Figure 2). The X-ray imaging results presented in Figure 3 further validate the effectiveness of the nanoplasmonic scintillator system in practical use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancements in both light yield and decay time have been shown to significantly improve the spatial resolution of Xray imaging, as demonstrated in Refs. [37,39] Since we have developed a Purcell-enhanced scintillator system facilitated by nanoplasmonic design (depicted in Figure 2). The X-ray imaging results presented in Figure 3 further validate the effectiveness of the nanoplasmonic scintillator system in practical use.…”
Section: Resultsmentioning
confidence: 99%
“…The Purcell effect has been applied to various photonic technologies such as single-photon sources, fluorescence imaging, and thermal emitters. [33,34] However, the study of the Purcell effect in nanophotonic scintillators, especially in combination with other advances such as emerging materials and dopant engineering, is still in its infancy, with theoretical studies of Purcell-enhanced nanophotonic scintillators beginning only in 2020, [29,30,[35][36][37][38] swiftly followed by experimental demonstrations on enhanced X-ray imaging using 2D photonic crystal scintillators, [31] and on decay rate enhancement in scintillators with few-hundred-microsecond decay times. [39] Notably, all studies of nanophotonic scintillators to date have been limited to photonic crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…The effect is sensitive to the thickness uniformity of LYSO layers: a standard deviation of 6–7 nm for an 800-layer structure (total thickness of ∼220 μm) destroys the effect. Furthermore, it was shown that a multilayer structure with varying thicknesses for different layers, given their thicknesses are accurately optimized, could also be efficient Purcell effect structures, potentially improving spatial resolution in imaging applications . Bizarri et al suggest using another side of the Purcell effect to shift a scintillator’s emission spectrum to better match the photodetector’s quantum efficiency, which can give up to a 2-fold increase in a photodetector output signal.…”
Section: Enhancement Of Time Resolution By a Meta-scintillation Approachmentioning
confidence: 99%
“…Furthermore, it was shown that a multilayer structure with varying thicknesses for different layers, given their thicknesses are accurately optimized, could also be efficient Purcell effect structures, potentially improving spatial resolution in imaging applications. 90 Bizarri et al 91 suggest using another side of the Purcell effect to shift a scintillator’s emission spectrum to better match the photodetector’s quantum efficiency, which can give up to a 2-fold increase in a photodetector output signal. Lately, Ye et al 92 experimentally showed the nanoplasmonic Purcell effect in (BA) 2 PbBr 4 perovskite thin film deposited on top of HfO 2 -covered Au layer.…”
Section: Enhancement Of Time Resolution By a Meta-scintillation Approachmentioning
confidence: 99%
“…[5,6] Accordingly, developing more convenient and cost-saving X-ray detector to obtain accurate information is an urgent need. [4] Current researches focused on developing new scintillator materials, [7,8] simplifying the corresponding manufacturing procedure, [9] designing the device structure, [10] and thereby improving the resolution of X-ray imaging [11,12] are underway. Although many successes have been achieved, the issues of scattering and optical crosstalk in X-ray imaging have not been properly solved, which seriously affects the realization of high-resolution imaging.…”
Section: Introductionmentioning
confidence: 99%